Sextarianism sovereignty, secularism, and the state in Lebanon - Mikdashi, Maya (Stanford University Press, 2022)
Cover -- Title Page -- Copyright -- Contents -- Preface -- Introduction. Sextarianism -- 1. Afterlives of a Census: Rethinking State Power and Political Difference -- 2. A Fire in the Archive: History, Ethnography, Multiplicity -- 3. Regulating Conversion: Sovereignty, Bureaucracy, and the Banality of Religion -- 4. Are You Going to Pride? Evangelical Secularism and the Politics of Law -- 5. The Epidermal State: Violence and the Materiality of Power -- Epilogue -- Acknowledgments -- Notes -- Bibliography -- Index -- Back Cover.